Inculcation of basic concepts of integrated water resources management based on video animation - Dani Achmad Fiqri Setiawan (Universitas Pendidikan Indonesia, 2023)
The younger generation can be competent in contributing to maintaining the continuity and quality of water resources; therefore, it is prioritized that they have an understanding of the basic concepts of integrated water resources management. This service activity collaborates with the Al-Mabrur Mosque madrasah and the Baleendah Permai Complex community to carry out integrated water resources management (PSDAT) outreach activities. This activity aims to instill basic concepts of PSDAT knowledge in madrasah children so that they will be ready to contribute to implementing PSDAT in their surrounding environment. This PSDAT integrated water resources management outreach activity uses the outreach method. The outreach media used is audio-visual media in the form of animated videos. The participants in this PSDAT educational activity were Al-Mabrur Mosque madrasah children who were still in elementary school. Counseling participants began to understand the knowledge and examples of activities regarding integrated water resources management. Participants were very enthusiastic about implementing the knowledge they had gained in the Baleendah Complex environment. Abstrak Generasi muda dapat berkompeten dalam berkontribusi menjaga kelangsungan dan kualitas sumber daya air, oleh karena itu diutamakan mereka harus memiliki pemahaman tentang konsep dasar dari pengelolaan sumber daya air terpadu. Kegiatan pengabdian ini bekerja sama dengan madrasah Masjid Al-Mabrur dan masyarakat Komplek Baleendah Permai untuk melaksanakan kegiatan penyuluhan tentang pengelolaan sumber daya air terpadu (PSDAT). Kegiatan ini bertujuan untuk menanamkan konsep dasar pengetahuan PSDAT pada anak-anak madrasah, sehingga mereka nantinya akan siap untuk berkontribusi dalam penyelenggaraan PSDAT di lingkungan sekitarnya. Kegiatan penyuluhan pengelolaan sumber daya air terpadu PSDAT ini menggunakan metode penyuluhan. Media penyuluhan yang digunakan adalah media audio-visual berupa video animasi. Adapun yang menjadi peserta kegiatan edukasi PSDAT ini adalah anak-anak madrasah Masjid Al-Mabrur yang masih duduk dibangku sekolah dasar. Peserta penyuluhan mulai memahami dan mengerti pengetahuan beserta contoh kegiatan seputar pengelolaan sumber daya air terpadu, peserta sangat antusias untuk mengimplementasikan pengetahuan yang telah didapatkannya di lingkungan Komplek Baleendah. Kata Kunci: Kuliah kerja nyata; KKN; sumber daya air; video animasi